Converter slag-containing compound, preparation method thereof and smelting method of high-phosphorus steel
By preparing the complex containing the residue, the problem of low utilization rate and high smelting cost of high phosphorus steel is solved, and the effect of efficient use of transfer stabs and reducing smelting costs is achieved.
Patent Information
- Application Number
- CN202411468056.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-28
AI Technical Summary
The overall utilization rate of converter slag is low, resulting in limited recycling in the steel industry and the smelting cost of high-phosphorus steel is high.
By preparing a complex containing a residue, the specific steps include crushing and screening of the rotor residue, mixing and reducing agents and adhesives, mixing and heating treatment to form a ball -shaped complex. The content of the composite rotary residue is 45%-80%, the reducing agent is 18%-50%, and the adhesive is 2%-6%.
The high value utilization of turntable residue is achieved, the smelting efficiency of high phosphorus steel is improved, the cost of smelting costs is reduced, and the utilization rate of the valuable element is improved.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of steel smelting, and in particular to a composite material containing converter slag and a preparation method thereof, and a smelting method of high-phosphorus steel. Background Art
[0002] Converter slag is waste slag produced in the converter steelmaking process, which mainly comes from oxides formed by oxidation of elements contained in molten iron and scrap steel. Due to the large base of steel production in my country, a large amount of converter slag is produced every year, which is piled up or discarded, which is not conducive to green development. At present, the comprehensive utilization rate of converter slag in my country is low, and the utilization level is relatively backward. Most of it belongs to primary utilization, usually used for road construction, cement production, backfilling engineering materials and return sintering. In addition, converter slag contains a large amount of valuable elements such as Fe, Mn, Mg, etc., and valuable elements are difficult to recycle. In particular, converter slag contains a large amount of dephosphorization products, which limits its recycling in the field of steelmaking.
[0003] Therefore, how to make full use of converter slag to create economic, environmental and social benefits for the steel industry has become a technical problem that needs to be solved urgently. Summary of the invention
[0004] The embodiments of the present application provide a composite material containing converter slag, a preparation method thereof, and a smelting method of high-phosphorus steel, which can achieve high-value utilization of waste converter slag and reduce the smelting cost of high-phosphorus steel.
[0005] In a first aspect, an embodiment of the present application proposes a composite material containing converter slag. Taking the total mass of the composite material containing converter slag as 100%, the composite material containing converter slag includes components in the following contents: converter slag: 45%-80%, reducing agent: 18%-50%, and adhesive: 2%-6%.
[0006] According to one aspect of an embodiment of the present application, the mass ratio of converter slag to reducing agent is (2-4):1.
[0007] According to one aspect of an embodiment of the present application, based on the total mass of the converter slag as 100%, the converter slag includes components with the following contents: calcium oxide: 20%-40%, silicon dioxide: 10%-20%, aluminum oxide: 2%-5%, manganese oxide: 2%-5%, magnesium oxide: 5%-10%, phosphorus pentoxide: 2%-10%, and the rest are iron oxides and a small amount of unavoidable impurities.
[0008] According to one aspect of an embodiment of the present application, the mass ratio of calcium oxide to silicon dioxide in converter slag is 1.5-4, and can be optionally 2-3.
[0009] According to one aspect of an embodiment of the present application, the reducing agent includes a metal reducing agent and / or a carbon-containing reducing agent; the metal reducing agent includes one or more of aluminum, silicon and their alloys with iron, and the carbon-containing reducing agent includes one or more of graphite powder, carbon powder, coke powder, activated carbon, biochar, lignite, anthracite and bituminous coal.
[0010] In the second aspect, an embodiment of the present application proposes a method for preparing a composite material containing converter slag, comprising: crushing and screening the converter slag to obtain the screened converter slag; mixing the screened converter slag with a reducing agent, and simultaneously stirring and heating the mixture to reach a target temperature, adding a binder for pelletizing, and obtaining a composite material containing converter slag; wherein the converter slag, the reducing agent and the binder are mixed according to the components and content ratios of the composite material of the first aspect of the present application.
[0011] According to another aspect of an embodiment of the present application, in the step of crushing and screening the converter slag to obtain the screened converter slag, the particle size of the screened converter slag is ≤20 mm.
[0012] According to another aspect of an embodiment of the present application, the screened converter slag is mixed with a reducing agent, and stirred and heated at the same time. After reaching the target temperature, an adhesive is added for pelletizing. In the step of obtaining a composite containing converter slag, the stirring time is 5-15 minutes, and the heating temperature is 1200-1300°C.
[0013] In a third aspect, an embodiment of the present application provides a method for smelting high-phosphorus steel, including the composite material of the first aspect of the present application or the composite material prepared by the preparation method of the second aspect of the present application.
[0014] According to another aspect of an embodiment of the present application, the smelting method includes: performing converter smelting on scrap steel and molten iron to obtain molten steel after converter smelting; refining the molten steel after converter smelting to obtain refined molten steel; wherein, during the steel tapping process of converter smelting, a composite material containing converter slag is added to the bottom of the ladle, and an inert gas is blown in for stirring.
[0015] According to another aspect of an embodiment of the present application, the smelting method includes: performing converter smelting on scrap steel and molten iron to obtain molten steel after converter smelting; refining the molten steel after converter smelting to obtain refined molten steel; and adding a compound containing converter slag during the refining process.
[0016] In the embodiment of the present application, by preparing converter slag into a composite containing converter slag, the various components in the converter slag composite can be mixed more evenly. By controlling the contents of converter slag, reducing agent and adhesive in the composite within a specific range, the valuable elements in the composite containing converter slag can be reduced, and the valuable elements in the converter slag can be efficiently utilized, thereby achieving high-value utilization of waste converter slag and reducing the cost of smelting high-phosphorus steel. DETAILED DESCRIPTION
[0017] The features and exemplary embodiments of various aspects of the present application will be described in detail below. In order to make the purpose, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only intended to explain the present application, rather than to limit the present application. For those skilled in the art, the present application can be implemented without the need for some of these specific details. The following description of the embodiments is only to provide a better understanding of the present application by illustrating the examples of the present application. In addition, the features, structures or characteristics described hereinafter may be combined in one or more embodiments in any suitable manner.
[0018] It should be noted that, in this application, the term "comprises" or any other variant thereof is intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprises..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0019] Unless otherwise specified, the values of the parameters mentioned in this application can be measured by various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application). Unless otherwise specified, the test temperature of the parameters mentioned in this application is 25° C. and the test pressure is standard atmospheric pressure.
[0020] A list of items connected by the term "one or more of" may mean any combination of the listed items. The term "plurality" means more than two.
[0021] Converter slag is a solid waste generated during the converter smelting process, and contains a large amount of phosphorus. Normally, phosphorus is one of the harmful elements in steel, which can cause problems such as cold brittleness and reduced low-temperature toughness of steel. However, adding appropriate phosphorus to high-phosphorus steel can increase the strength of the steel or improve the corrosion resistance of the steel. The production of high-phosphorus steel is generally carried out through a converter smelting process, but due to the oxidizing atmosphere in the converter, the phosphorus in the molten iron will be removed during the smelting process. The phosphorus content in the molten steel after the converter smelting is generally low. Therefore, in the smelting process of high-phosphorus steel, it is necessary to increase the phosphorus content in the molten steel after converter smelting.
[0022] In view of this, an embodiment of the present application proposes a composite material containing converter slag. Taking the total mass of the composite material containing converter slag as 100%, the composite material containing converter slag includes components with the following contents: converter slag: 45%-80%, reducing agent: 18%-50%, and adhesive: 2%-6%.
[0023] The embodiment of the present application prepares converter slag into a composite containing converter slag, so that the various components in the converter slag composite can be mixed more evenly. The contents of converter slag, reducing agent and adhesive in the composite can be controlled within a specific range, and the valuable elements in the composite containing converter slag can be reduced to achieve efficient utilization of the valuable elements in the converter slag, thereby achieving high-value utilization of waste converter slag and reducing the smelting cost of high-phosphorus steel.
[0024] It should be noted that the composite material containing converter slag is in the form of pellets, and the particle size of the pellets is ≤40 mm.
[0025] In some optional embodiments, the mass ratio of converter slag to reducing agent can be (2-4): 1. For example, it can be 2: 1, 2.5: 1, 3: 1, 3.5: 1, 4: 1, or a range consisting of any two of the above values. If the mass ratio is too low, the reduction degree of phosphorus pentoxide, iron oxides and manganese oxides in the converter slag is low, which affects the subsequent use effect of the composite; if the mass ratio is too high, the excess reducing agent is burned, resulting in material waste and cost increase.
[0026] Adding a binder to the powder mixture is beneficial for the powder mixture to form a block solid. When the mass content of the binder is within the above range, the powder mixture can be better bonded into a block.
[0027] In some optional embodiments, the adhesive may include one or more of an inorganic adhesive, an organic adhesive, and an organic-inorganic composite adhesive. For example, the inorganic adhesive may include one or both of bentonite and slaked lime. The organic adhesive may include one or both of peridot and modified starch.
[0028] In order to form the powder mixture into a bulk solid, a small amount of water needs to be added to the powder mixture.
[0029] In some optional embodiments, based on the total mass of the converter slag as 100%, the converter slag may include components with the following contents: calcium oxide: 20%-40%, silicon dioxide: 10%-20%, aluminum oxide: 2%-5%, manganese oxide: 2%-5%, magnesium oxide: 5%-10%, phosphorus pentoxide: 2%-10%, and the rest are iron oxides and unavoidable impurities.
[0030] In the embodiment of the present application, the iron oxide may include one or more of ferrous oxide, ferric oxide or ferric oxide. It is understood that by adding a reducing agent to the composite containing converter slag, the above iron oxide can be reduced to elemental iron, thereby realizing the reuse of the iron oxide. The amount of the reducing agent is mainly determined according to the content of manganese oxide, phosphorus pentoxide and iron oxide in the converter slag.
[0031] In some optional embodiments, the mass ratio of calcium oxide to silicon dioxide in the converter slag may be 1.5-4, and may be 2-3.
[0032] In some optional embodiments, the reducing agent may include a metallic reducing agent and / or a carbonaceous reducing agent.
[0033] In some optional embodiments, the metal reducing agent may include one or more of aluminum, silicon, and alloys thereof with iron.
[0034] In some optional embodiments, the carbonaceous reducing agent may include one or more of graphite powder, carbon powder, coke powder, activated carbon, biochar, lignite, anthracite and bituminous coal.
[0035] The reducing agent can reduce most of the phosphorus pentoxide, iron oxides and manganese oxides in the converter slag to their corresponding elements.
[0036] Carbon-containing reducing agents are cheap and low in cost. Using powdered carbon-containing reducing agents can make the reduction more complete. Metal reducing agents have better reduction effects, and the metal reducing agents that are not fully reacted can also be used as additives in the refining process.
[0037] In some optional embodiments, the average particle size of the carbonaceous reducing agent is ≥50 mesh.
[0038] In some optional embodiments, the average particle size of the metal reducing agent is ≤3 mm.
[0039] In the embodiments of the present application, by selecting the reducing agent within the above-mentioned particle size range, the reducing agent can better cooperate with the converter slag, thereby further improving the recovery rate of the valuable elements in the converter slag.
[0040] The present application embodiment provides a method for preparing a composite material containing converter slag. The preparation method comprises the following steps:
[0041] S10: crushing and screening the converter slag to obtain screened converter slag;
[0042] S20: mixing the sieved converter slag with a reducing agent, stirring and heating the mixture until the target temperature is reached, and then adding a binder to pelletize the mixture to obtain a composite containing converter slag;
[0043] The converter slag, the reducing agent and the adhesive are mixed according to the components and content ratio of the composite material of the present application.
[0044] The above-mentioned preparation method can achieve a good composite effect of converter slag and reducing agent, thereby preparing converter slag with uniform mixing of various components.
[0045] It should be noted that the converter slag before screening is still at a relatively high temperature, thereby reducing the energy consumption of the heating treatment.
[0046] In some optional embodiments, in the step of crushing and screening the converter slag to obtain the screened converter slag, the particle size of the screened converter slag is ≤20 mm.
[0047] In the embodiment of the present application, the particle size of the converter slag after screening is controlled within the above range, which can increase the contact area between the converter slag and the reducing agent, improve the efficiency of the reduction reaction, and thus improve the utilization rate of the converter slag.
[0048] In the embodiments of the present application, there is no limitation on the equipment for crushing and pelletizing. The crushing can be performed using a ball mill, and the pelletizing can be performed using a pellet press. The powder mixture can be prepared into a block solid. The crushing, heating, pelletizing and other processing operations can also be performed in the same dedicated equipment.
[0049] It should be noted that a small amount of water needs to be added during the pelletizing process during the preparation process, so the pelletized lumps need to be heated to remove the moisture in the lumps.
[0050] In some optional embodiments, the screened converter slag is mixed with a reducing agent, and stirred and heated at the same time. After reaching the target temperature, a binder is added for pelletizing. In the step of obtaining a composite containing converter slag, the stirring time can be 5-15 minutes, and the heating temperature can be 1200-1300°C.
[0051] The embodiment of the present application sets the stirring treatment time within the above range, so that the converter slag and the reducing agent can fully react and improve the reduction ratio of the converter slag. The temperature of the heating treatment is controlled within the above range, which can meet the thermodynamic conditions for the reduction of the converter slag and improve the reaction speed.
[0052] The "target temperature" is 1200-1300° C. When the binder is added, the temperature of the mixture of the screened converter slag and the reducing agent has dropped to 20-60° C.
[0053] The embodiments of the present application provide a method for smelting high-phosphorus steel, and the smelting method includes the composite of the present application or the composite prepared by the preparation method of the present application.
[0054] The composite containing converter slag prepared in the present application or the composite containing converter slag prepared by the preparation method of the present application is applied to the smelting of high-phosphorus steel, which can achieve high-value utilization of waste converter slag while reducing the smelting cost of high-phosphorus steel.
[0055] In some optional embodiments, the smelting method comprises the following steps:
[0056] Perform converter smelting on scrap steel and molten iron to obtain molten steel after converter smelting;
[0057] Refining the molten steel after converter smelting to obtain refined molten steel;
[0058] In the process of tapping the converter, a composite material containing converter slag is added to the bottom of the ladle, and an inert gas is blown in for stirring.
[0059] In some optional embodiments, the inert gas may be argon or nitrogen.
[0060] In some optional embodiments, the flow rate of the inert gas may be 280-320 L / min.
[0061] In some alternative embodiments, the composite containing converter slag is added during the refining process.
[0062] In the embodiment of the present application, a composite material containing converter slag is added during the converter steel-making process or during the refining process, thereby reducing the amount of other slag-forming agents added during the refining process.
[0063] It should be noted that the amount of the composite containing converter slag added can be calculated based on the target phosphorus content of the steel grade and the weight of the molten steel.
[0064] Example
[0065] The following examples describe the disclosure of the present application in more detail, and these examples are for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further treatment, and the instruments used in the examples are commercially available.
[0066] Example 1
[0067] (1) Composition of converter slag
[0068] The composition and content of the converter slag in Example 1 are shown in Table 1.
[0069] Table 1
[0070] Element <![CDATA[P2O5]]> MnO CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> TFe Alkalinity content 8.5% 4.2% 33.7% 7.3% 15.1% 3.4% 23.5% 2.23
[0071] (2) Preparation of composite materials containing converter slag
[0072] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0073] Add 200kg of graphite powder to the equipment, turn on the heating and stirring functions at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0074] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0075] (3) Smelting of high phosphorus steel
[0076] The above-mentioned composite material containing converter slag was applied to the 210-ton converter smelting high-phosphorus steel process. During the steel tapping process after the converter smelting was completed, 500 kg of the above-mentioned composite material was added to the ladle, and the steel tapping process was accompanied by argon stirring, and the argon flow rate was 300 L / min.
[0077] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 95.6%.
[0078] The calculation formula of the P element recovery rate is: (P content at the refining station - P content at the refining station) * weight of molten steel at the refining station / (amount of compound added * P content of the compound).
[0079] Example 2
[0080] (1) Composition of converter slag
[0081] The composition and content of the converter slag in Example 2 are shown in Table 2.
[0082] Table 2
[0083] Element <![CDATA[P2O5]]> MnO CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> TFe Alkalinity content 8.5% 4.2% 33.7% 7.3% 15.1% 3.4% 23.5% 2.23
[0084] (2) Preparation of composite materials containing converter slag
[0085] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0086] Add 200kg of graphite powder to the equipment, turn on the heating and stirring functions at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0087] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0088] (3) Smelting of high phosphorus steel
[0089] The composite containing converter slag was applied to the 210-ton converter in the process of smelting high-phosphorus steel. During the LF furnace refining process, 500 kg of the composite was added to the ladle.
[0090] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 95.8%.
[0091] Example 3
[0092] (1) Composition of converter slag
[0093] The composition and content of the converter slag in Example 3 are shown in Table 3.
[0094] Table 3
[0095] Element <![CDATA[P2O5]]> MnO CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> TFe Alkalinity content 8.5% 4.2% 33.7% 7.3% 15.1% 3.4% 22.5% 2.23
[0096] (2) Preparation of composite materials containing converter slag
[0097] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0098] Add 250kg of graphite powder to the equipment, turn on the heating and stirring functions at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0099] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0100] (3) Smelting of high phosphorus steel
[0101] The above-mentioned composite material containing converter slag was applied to the 210-ton converter smelting high-phosphorus steel process. During the steel tapping process after the converter smelting was completed, 500 kg of the above-mentioned composite material was added to the ladle, and the steel tapping process was accompanied by argon stirring, and the argon flow rate was 300 L / min.
[0102] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 96.2%.
[0103] Example 4
[0104] (1) Composition of converter slag
[0105] The composition and content of the converter slag in Example 4 are shown in Table 4.
[0106] Table 4
[0107] Element <![CDATA[P2O5]]> MnO CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> TFe Alkalinity content 8.5% 4.2% 33.7% 7.3% 15.1% 3.4% 22.5% 2.23
[0108] (2) Preparation of composite materials containing converter slag
[0109] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0110] Then add 350kg of carbon powder to the equipment, turn on the heating function and stirring function at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0111] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0112] (3) Smelting of high phosphorus steel
[0113] The above-mentioned composite material containing converter slag was applied to the 210-ton converter smelting high-phosphorus steel process. During the steel tapping process after the converter smelting was completed, 500 kg of the above-mentioned composite material was added to the ladle, and the steel tapping process was accompanied by argon stirring, and the argon flow rate was 300 L / min.
[0114] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 97.5%.
[0115] Example 5
[0116] (1) Composition of converter slag
[0117] The composition and content of the converter slag in Example 5 are shown in Table 5.
[0118] Table 5
[0119] Element <![CDATA[P2O5]]> MnO CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> TFe Alkalinity content 8.5% 4.2% 33.7% 7.3% 15.1% 3.4% 22.5% 2.23
[0120] (2) Preparation of composite materials containing converter slag
[0121] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0122] Then add 175kg of graphite powder to the equipment, turn on the heating and stirring functions at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0123] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0124] (3) Smelting of high phosphorus steel
[0125] The above-mentioned composite material containing converter slag was applied to the 210-ton converter smelting high-phosphorus steel process. During the steel tapping process after the converter smelting was completed, 500 kg of the above-mentioned composite material was added to the ladle, and the steel tapping process was accompanied by argon stirring, and the argon flow rate was 300 L / min.
[0126] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 94.6%.
[0127] Example 6
[0128] (1) Composition of converter slag
[0129] The composition and content of the converter slag in Example 6 are shown in Table 6.
[0130] Table 6
[0131] Element <![CDATA[P2O5]]> MnO CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> TFe Alkalinity content 8.5% 4.2% 33.7% 7.3% 15.1% 3.4% 22.5% 2.23
[0132] (2) Preparation of composite materials containing converter slag
[0133] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0134] Then add 350kg of graphite powder to the equipment, turn on the heating and stirring functions at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0135] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0136] (3) Smelting of high phosphorus steel
[0137] The above-mentioned composite material containing converter slag was applied to the 210-ton converter smelting high-phosphorus steel process. During the steel tapping process after the converter smelting was completed, 500 kg of the above-mentioned composite material was added to the ladle, and the steel tapping process was accompanied by argon stirring, and the argon flow rate was 300 L / min.
[0138] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 98.7%.
[0139] Example 7
[0140] (1) Composition of converter slag
[0141] The composition and content of the converter slag in Example 7 are shown in Table 7.
[0142] Table 7
[0143] Element <![CDATA[P2O5]]> MnO CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> TFe Alkalinity content 8.8% 3.2% 41.7% 6.9% 12.9% 3.1% 21.4% 3.23
[0144] (2) Preparation of composite materials containing converter slag
[0145] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0146] Add 200kg of graphite powder to the equipment, turn on the heating and stirring functions at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0147] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0148] (3) Smelting of high phosphorus steel
[0149] The above-mentioned composite material containing converter slag was applied to the 210-ton converter smelting high-phosphorus steel process. During the steel tapping process after the converter smelting was completed, 500 kg of the above-mentioned composite material was added to the ladle, and the steel tapping process was accompanied by argon stirring, and the argon flow rate was 300 L / min.
[0150] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 94.1%.
[0151] Example 8
[0152] (1) Composition of converter slag
[0153] The composition and content of the converter slag in Example 8 are shown in Table 8.
[0154] Table 8
[0155] Element <![CDATA[P2O5]]> MnO CaO MgO <![CDATA[SiO2]]> <![CDATA[Al2O3]]> TFe Alkalinity content 5.4% 3.9% 30.7% 6.9% 15.1% 3.4% 24.5% 2.04
[0156] (2) Preparation of composite materials containing converter slag
[0157] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0158] Add 200kg of graphite powder to the equipment, turn on the heating and stirring functions at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0159] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0160] (3) Smelting of high phosphorus steel
[0161] The above-mentioned composite material containing converter slag was applied to the 210-ton converter smelting high-phosphorus steel process. During the steel tapping process after the converter smelting was completed, 500 kg of the above-mentioned composite material was added to the ladle, and the steel tapping process was accompanied by argon stirring, and the argon flow rate was 300 L / min.
[0162] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 95.8%.
[0163] Comparative Example
[0164] The composition of converter slag is the same as that in Example 1.
[0165] (1) Preparation of composite materials containing converter slag
[0166] 700 kg of high-temperature converter slag is placed in a special device for crushing to obtain converter slag with a particle size of ≤10 mm;
[0167] Then add 50kg of graphite powder to the equipment, turn on the heating and stirring functions at the same time, and continue stirring for 10 minutes after reaching the target temperature of 1250℃;
[0168] Then, 50 kg of organic adhesive modified starch was added into the equipment for pelletization to obtain a composite material containing converter slag.
[0169] (2) Smelting of high phosphorus steel
[0170] The above-mentioned composite material containing converter slag was applied to the 210-ton converter smelting high-phosphorus steel process. During the steel tapping process after the converter smelting was completed, 500 kg of the above-mentioned composite material was added to the ladle, and the steel tapping process was accompanied by argon stirring, and the argon flow rate was 300 L / min.
[0171] The recovery rate of P element in molten steel after refining treatment was tested and calculated to be 88.6%.
[0172] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.
Claims
1. A composite material containing converter slag, characterized in that: Taking the total mass of the composite material containing converter slag as 100%, the composite material containing converter slag comprises the following components: converter slag: 45%-80%, reducing agent: 18%-50%, and adhesive: 2%-6%.
2. The composite according to claim 1, characterized in that The mass ratio of the converter slag to the reducing agent is (2-4):
1.
3. The composite according to claim 1, characterized in that Taking the total mass of the converter slag as 100%, the converter slag includes components in the following contents: calcium oxide: 20%-40%, silicon dioxide: 10%-20%, aluminum oxide: 2%-5%, manganese oxide: 2%-5%, magnesium oxide: 5%-10%, phosphorus pentoxide: 2%-10%, and the rest are iron oxides and a small amount of inevitable impurities.
4. The composite according to claim 3, characterized in that The mass ratio of calcium oxide to silicon dioxide in the converter slag is 1.5-4, and can be optionally 2-3.
5. The composite according to claim 1, characterized in that The reducing agent includes a metal reducing agent and / or a carbonaceous reducing agent; The metal reducing agent includes one or more of aluminum, silicon and alloys thereof with iron, and the carbon-containing reducing agent includes one or more of graphite powder, carbon powder, coke powder, activated carbon, biochar, lignite, anthracite and bituminous coal.
6. A method for preparing a composite containing converter slag, characterized in that: include: Performing crushing and screening treatments on the converter slag to obtain screened converter slag; The sieved converter slag is mixed with a reducing agent, and stirred and heated at the same time, and after reaching a target temperature, a binder is added to perform pelletization to obtain a composite containing converter slag; The converter slag, the reducing agent and the adhesive are mixed according to the components and content ratio of the composite according to any one of claims 1 to 5.
7. The preparation method according to claim 6, characterized in that: In the step of crushing and screening the converter slag to obtain the screened converter slag, the particle size of the screened converter slag is ≤20 mm.
8. The preparation method according to claim 6, characterized in that: The screened converter slag is mixed with a reducing agent, and stirred and heated at the same time, and a binder is added for pelletizing after reaching the target temperature to obtain a composite containing converter slag, wherein the stirring time is 5-15 minutes, and the heating temperature is 1200-1300°C.
9. A method for smelting high-phosphorus steel, characterized in that: The invention comprises the complex described in any one of claims 1 to 5 or the complex prepared by the preparation method described in any one of claims 6 to 8.
10. The smelting method according to claim 9, characterized in that: include: Perform converter smelting on scrap steel and molten iron to obtain molten steel after converter smelting; Refining the molten steel after converter smelting to obtain refined molten steel; Wherein, during the steel tapping process of the converter smelting, a composite material containing converter slag is added to the bottom of the ladle, and an inert gas is blown in for stirring; and / or, A composite material containing converter slag is added during the refining process.